The Role of Early Childhood Education Teachers in Detecting and Addressing Mental Health Issues in Young Children at Kindergarten Cluster II, Seteluk District - Anggun Berliantina; Baik Nilawati Astini; Ika Rachmayani; Gunawan Gunawan (Indonesian Publication Center, 2025)
This study investigates the role of Early Childhood Education (ECE) teachers in detecting and addressing mental health issues among young children in Kindergarten Cluster II, Seteluk District. Employing a quantitative approach with a survey design, data were collected through questionnaires distributed to 44 teachers across 16 kindergartens. The data were analyzed using simple linear regression with SPSS 30.0. The results indicate that the teacher's role significantly influences the detection and management of mental health problems in early childhood. A regression coefficient of -0.864 was obtained, indicating an inverse relationship: as the teacher's role increases, the level of mental health problems in children decreases. Furthermore, the R-Square value of 0.302 suggests that 30.2% of the variance in children's mental health issues is attributed to the teacher's role. Consequently, teachers play a pivotal role in identifying and mitigating mental health challenges. The study recommends continuous training and collaboration among teachers, parents, and professionals to foster a healthy, supportive environment for early childhood development.